The Effectiveness of Technology Based Financial Accounting Instruction: A Literature Study at SMK 1 Sinjai - Ramadhani, Magfirah Wahyu (Universitas Negeri Makassar, 2025)
This study aims to analyze the effectiveness of technology-based financial accounting learning in Vocational High Schools (SMK) through a literature review approach. The review was conducted by examining various literature sources, including journals, scientific articles, and relevant research reports published between 2017 and 2025. The analysis employed a descriptive qualitative method by highlighting the role of technology in improving students’ conceptual understanding, practical skills, and learning motivation in financial accounting subjects. The findings indicate that the use of technology—such as accounting software, online learning applications, and interactive media—significantly enhances the effectiveness of the learning process. The success of implementing technology-based learning is also strongly influenced by teacher readiness, school infrastructure support, and the alignment of learning methods with student characteristics. In addition, the application of technology-based learning helps strengthen students’ digital competencies and fosters critical and collaborative thinking skills required in the modern workplace. Therefore, it is necessary to develop an adaptive curriculum, enhance teacher capacity, and provide adequate technology-based learning facilities to continuously improve the effectiveness of financial accounting learning in Vocational High Schools.Penelitian ini bertujuan untuk menganalisis efektivitas pembelajaran akuntansi keuangan berbasis teknologi di Sekolah Menengah Kejuruan (SMK) melalui pendekatan tinjauan literatur. Tinjauan ini dilakukan dengan memeriksa berbagai sumber literatur, termasuk jurnal, artikel ilmiah, dan laporan penelitian yang relevan yang diterbitkan antara tahun 2017 hingga 2025. Analisis ini menggunakan metode deskriptif kualitatif dengan menyoroti peran teknologi dalam meningkatkan pemahaman konseptual siswa, keterampilan praktis, dan motivasi belajar dalam mata pelajaran akuntansi keuangan. Hasil temuan menunjukkan bahwa penggunaan teknologi—seperti perangkat lunak akuntansi, aplikasi pembelajaran daring, dan media interaktif—secara signifikan meningkatkan efektivitas proses pembelajaran. Keberhasilan penerapan pembelajaran berbasis teknologi juga sangat dipengaruhi oleh kesiapan guru, dukungan infrastruktur sekolah, dan kesesuaian metode pembelajaran dengan karakteristik siswa. Selain itu, penerapan pembelajaran berbasis teknologi membantu memperkuat kompetensi digital siswa dan memupuk keterampilan berpikir kritis serta kolaboratif yang dibutuhkan di tempat kerja modern. Oleh karena itu, perlu untuk mengembangkan kurikulum yang adaptif, meningkatkan kapasitas guru, dan menyediakan fasilitas pembelajaran berbasis teknologi yang memadai untuk terus meningkatkan efektivitas pembelajaran akuntansi keuangan di Sekolah Menengah Kejuruan.